Workshop Pembuatan Minyak Telon - margareta retno; Kamilla Sekar; Sandy Mahesa Yudhantara (Universitas Pahlawan Tuanku Tambusai, 2022)
Telon oil is a product from Indonesia that has been known for a long time which can be developed to be made independently by the community. Objective provide an introduction to herbal plants that can be applied in the community. The approach method used is to provide an explanation of the scientific name or Latin name for herbal plants in Indonesia to class XII students of SMK Bhakti Kencana Kendal. Furthermore, an introduction to the types of herbal plants and herbal chemicals that will be used in the manufacture of telon oil is carried out, followed by formulating the composition of telon oil which will be made with fennel oil, eucalyptus oil and coconut oil. The result of the activity is that students are interested and able to apply pharmacognosy science and herbal chemicals into dosage forms that are beneficial to health, namely the manufacture of telon oil